Study on Addressing Shortages of Doctors through Department of Health Bursaries in Selected University of Kwa Zulu Natal Province, South Africa - Bongani Innocent Dlamini; Luther-King Junior Zogli; Mthembeni Mthethwa (Issues and Development in Health Research Vol. 5, 2021)
In an attempt to address scarcity of medical practitioners in South Africa, the Province of KwaZulu Natal’s Department of Health put in place a strategy to award bursaries to medical students in order to intensify the recruitment and retention of medical practitioners. Students who go through this programme will then have a service obligation to the department. The objective current study is therefore to determine whether the current process of awarding bursaries contributes to the bursary-holders’ satisfaction and loyalty to the Department of Health. It will find out the extent to which the process of awarding bursaries to medical students influences students’ loyalty to the department upon completion, other than the legal obligation which is enforced through a contractual agreement. This study adopted quantitative research design. The findings revealed that that majority of the participants are satisfied with guidance providing when completing bursary forms, response to application, being able to go to their university of choice and the monetary value of the bursary. However, it was noted that the bursary information is not well publicised in some districts. Furthermore, some students did not understand the bursary contract as well as were unaware of the consequences of breach of contract. Finally, most participants alluded to the fact that they are not provided the opportunity to give feedback about their experience of the bursary programme.